2016
DOI: 10.1128/aac.01050-16
|View full text |Cite
|
Sign up to set email alerts
|

Dual Targeting of Cell Wall Precursors by Teixobactin Leads to Cell Lysis

Abstract: Teixobactin represents the first member of a newly discovered class of antibiotics that act through inhibition of cell wall synthesis. Teixobactin binds multiple bactoprenol-coupled cell wall precursors, inhibiting both peptidoglycan and teichoic acid synthesis. Here, we show that the impressive bactericidal activity of teixobactin is due to the synergistic inhibition of both targets, resulting in cell wall damage, delocalization of autolysins, and subsequent cell lysis. We also find that teixobactin does not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(100 citation statements)
references
References 44 publications
1
96
0
3
Order By: Relevance
“…In contrast, most of the teixobactin analogues tested showed the same MIC across all the S. aureus strains, including Mu50. Hence, these teixobactin analogues, similar to the parent teixobactin, are unaffected by the thicker peptidoglycan layers in the VISA strains . On a side note, studies have suggested the addition of a surfactant in the broth microdilution assay to prevent possible adsorption of the peptide compounds to the plastic wall of the 96‐well plate .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, most of the teixobactin analogues tested showed the same MIC across all the S. aureus strains, including Mu50. Hence, these teixobactin analogues, similar to the parent teixobactin, are unaffected by the thicker peptidoglycan layers in the VISA strains . On a side note, studies have suggested the addition of a surfactant in the broth microdilution assay to prevent possible adsorption of the peptide compounds to the plastic wall of the 96‐well plate .…”
Section: Resultsmentioning
confidence: 99%
“…Teixobactin offers a potential solution to this predicament because it remains effective against MRSA, as well as the vancomycin‐intermediate S. aureus (VISA) due to its unique mode of action . It has been shown to synergistically block the biosyntheses of peptidoglycan and teichoic acid, thereby resulting in a weakened cell wall and autolysin‐mediated cell lysis …”
Section: Introductionmentioning
confidence: 99%
“…1,2 In reflection of this promise, the initial report has been cited more than 500 times. Teixobactin is a non-ribosomal cyclic undecadepsipeptide and contains the rare amino acid allo -enduracididine at position 10.…”
mentioning
confidence: 99%
“…Lediglich E.-coli-Mutanten mit einer defekten äußeren Membran sind anfällig,was darauf hindeutet, dass das Antibiotikum die äußere Membran von Gram-negativen Bakterien nicht durchdringen kann. [145] Die fehlende Resistenzentwicklung ist somit auf den multiplen Wirkmechanismus zurückzuführen;zudem adressiert Te ixobactin ein hochkonserviertes Nicht-Protein-Target. Beispielsweise lag in einem Maus-Sepsismodell einer intraperitonealen MRSA-Infektion der PD 50 -Wert (schützende Dosis,bei der die Hälfte der Tiere überleben) fürT eixobactin bei 0.2 mg pro kg, während Va ncomycin einen PD 50 -Wert von 2.75 mg pro kg aufweist.…”
Section: Teixobactinunclassified